Using PDP^-1 method.
Ok, I got this question wrong on a test.
Essentially, I had to find A = E1 + E2 where
A =
1 2 -2
0 5 -4
0 2 -1
satisfies
P^-1AP=
1 0 0
0 1 0
0 0 3
with P =
2 1 1
1 1 2
1 1 1
Ok, so..
E1 = PD1P^-1
E2 = PD2P^-1
Now, the correct answer shows:
D1 =
|1 0 0 |
|0 1 0|
|0 0 0|
D2 =
|0 0 0|
|0 0 0|
|0 0 1|
My question is why? Why couldn't it have been the other way around?
Ok, I got this question wrong on a test.
Essentially, I had to find A = E1 + E2 where
A =
1 2 -2
0 5 -4
0 2 -1
satisfies
P^-1AP=
1 0 0
0 1 0
0 0 3
with P =
2 1 1
1 1 2
1 1 1
Ok, so..
E1 = PD1P^-1
E2 = PD2P^-1
Now, the correct answer shows:
D1 =
|1 0 0 |
|0 1 0|
|0 0 0|
D2 =
|0 0 0|
|0 0 0|
|0 0 1|
My question is why? Why couldn't it have been the other way around?